2021
DOI: 10.3390/cells10081848
|View full text |Cite
|
Sign up to set email alerts
|

Gelsolin Contributes to the Motility of A375 Melanoma Cells and This Activity Is Mediated by the Fibrous Extracellular Matrix Protein Profile

Abstract: Skin melanocytes reside on the basement membrane (BM), which is mainly composed of laminin, collagen type IV, and proteoglycans. For melanoma cells, in order to invade into the skin, melanocytes must cross the BM. It has been reported that changes in the composition of the BM accompany melanocytes tumorigenesis. Previously, we reported high gelsolin (GSN)—an actin-binding protein—levels in melanoma cell lines and GSN’s importance for migration of A375 cells. Here we investigate whether melanoma cells migrate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…2 J and K). Finally, we analyzed the invasion potential of studied cells using Transwell ™ filters coated with Matrigel ™ that mimics the ECM [ 34 ]. Both ABCA1 KO and probucol-treated cells exhibited a reduced capacity for invading the ECM and migrating to the other side of the filter, which was reflected by a loss of more than 40% of invading cells when compared to scrambled and DMSO-treated cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 J and K). Finally, we analyzed the invasion potential of studied cells using Transwell ™ filters coated with Matrigel ™ that mimics the ECM [ 34 ]. Both ABCA1 KO and probucol-treated cells exhibited a reduced capacity for invading the ECM and migrating to the other side of the filter, which was reflected by a loss of more than 40% of invading cells when compared to scrambled and DMSO-treated cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the formin family member DIAPH2 [ 66 , 67 ], as well as integrin β5 (together with different α-chains) form the adhesive-protrusive domains of invadopodia [ 68 , 69 ]. It is noteworthy that gelsolin, an actin modulator associated with invadopodia [ 70 , 71 ], was elevated both transcriptionally and proteomically. The role of IDH, in invadopodia formation and matrix degradation is still unclear at the mechanistic level [ 39 ] and will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Published data showed that GSN played an important role in melanoma cell migration. GSN-depleted A375 melanoma cells exhibited a significantly impaired capacity to migrate on laminin, a primary component of the skin's basement membrane [34]. Changes in cellular morphology imply alteration of cell cytoskeleton proteins, including GSN that also plays an important role in cell invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%